Finite-time positiveness and distributed control of Lipschitz nonlinear multi-agent systems - Ren, Chengcheng; Nie, Rong; He, Shuping (Journal of the Franklin Institute, 2019)
The finite-time positiveness and distributed control problem is studied for a class of Lipschitz nonlinear multi-agent systems. The objective is to design a suitable distributed controller which makes the closed-loop multi-agent systems be positive and finite-time stabilizable and satisfy the given H∞ performance index. Sufficient conditions are initially established on the existence of the finite-time distributed controller by using proper multiple Lyapunov functions and the design criteria are presented in the form of linear matrix inequalities. Finally, an example of multi-agent systems with six agents is presented to illustrate the feasibility and validity of the proposed methods.